Pola Asuh Anak Keluarga yang Berbeda Kota Tempat Tinggal: Studi 3 Keluarga di Desa Tompongpatu - Andi Molawaliadda Patodongi (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to find out how the parenting style adopted by three families from different cities of residence in caring for the child. This research is a normative-empirical research using parenting theory. The results of research conducted on three couples who have different cities of residence are, even though the parents have different cities of residence, the parents still carry out childcare using generally known patterns such as: authoritative and democratic. Also using patterns with Islamic education such as: exemplary education, advice, and concern. Parenting using this pattern is considered very important because the child's behavior in the future depends on how the parenting style is applied by the parents even though one of the parents is not near the child.